Magnesium-calcium-zirconium-carbon brick and production method thereof
By using magnesium, calcium, zirconium carbon bricks prepared by sintered raw materials such as magnesium, calcium, zirconium sand, etc., the problems of hydration and insufficient thermal shock resistance and stability of traditional bricks are solved, and high performance performance in humid environments and high-temperature smelting environments are achieved.
Patent Information
- Application Number
- CN202510295504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional magnesium-calcium carbon bricks are prone to hydration in humid environments, resulting in reduced strength. In high-temperature smelting environments, the thermal shock stability and erosion resistance are insufficient, which cannot meet the strict requirements of the steel mill smelting environment.
Raw materials such as sintered magnesium calcium zirconium sand, zirconium oxide fine powder, silicon carbide fine powder, nano-scale yttrium oxide high-dispersible particles and C9 petroleum resin powder were prepared through high-temperature vertical kiln sintering and high-pressure molding processes to improve hydration resistance and improve thermal shock stability, corrosion resistance and flush resistance.
The bricks are significantly improved in hydration resistance, thermal shock stability, corrosion resistance and flush resistance, so that they can be stored in humid environments for a long time and adapt to the needs of the steel mill's high-temperature smelting environment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, in particular to a magnesium calcium zirconium carbon brick and a production method thereof. Background Art
[0002] The demand for steel is gradually decreasing, and steel mills have excess capacity. In order to reduce losses, steel mills have to reduce production and capacity and are forced to suspend production for maintenance. On the other hand, they have to reduce production costs and increase the proportion of scrap steel added. This is very unfavorable to the service life of refractory materials, and higher requirements are placed on the thermal shock stability, erosion resistance and corrosion resistance of refractory materials. With the upgrading of industry and the advancement of technology, the demand for high-quality steel grades and clean steel is increasing, and the smelting environment of steel mills has become more and more demanding on refractory materials. For example, the increase in the flow rate of stirring gases such as oxygen and argon, the extension of smelting time and the continuous increase in smelting temperature have also made the requirements for refractory materials more stringent. For example, when smelting some steel grades, the carbon content and alumina of bricks must be controlled within a certain range to prevent the increase of carbon and aluminum in molten steel during high-temperature smelting.
[0003] Traditional magnesium calcium carbon bricks introduce calcium on the basis of magnesium carbon bricks. CaO can purify molten steel, but it also makes the bricks easy to hydrate in a humid environment, resulting in brick powdering and severe reduction in strength. Steel mills are usually concentrated in coastal cities and built along the coast. The humid climate exacerbates the hydration of bricks. The intermittent masonry of some steel mills also increases the possibility of hydration. Traditional magnesium calcium carbon bricks have lower graphite addition than magnesium carbon bricks, and the corrosion resistance and thermal shock resistance are also reduced accordingly. It can be seen from this that it is urgent to study a new type of refractory brick. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention introduces sintered magnesium calcium zircon sand, zirconium oxide powder, silicon carbide powder, nano-scale yttria high dispersion particles and C9 petroleum resin powder. It can significantly improve the anti-hydration performance, improve the thermal shock stability, corrosion resistance and scouring resistance of bricks. It can also be stored for a long time in a humid environment, and more importantly, it can adapt to the smelting environment of a steel plant.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a magnesium calcium zirconium carbon brick and a production method thereof.
[0006] Magnesium calcium zirconium carbon bricks are made of the following raw materials and their weight ratios: Sintered magnesium calcium zirconium sand 60% ~ 80%; Fused magnesia 10% to 30%; Zirconia 2% to 4%; Silicon carbide powder 0.5%~3%; Nano yttrium oxide highly dispersed particles 2% to 6%; C9 petroleum resin powder 1%~2%; Graphite 2% to 7%; Binder 4% to 6%; Hexamethylenetetramine 0.3% to 0.5%; Wherein: the sintered magnesium calcium zirconium sand with a particle size of 5-3 mm has a ratio of 19%-36%, the particle size of 3-1 mm has a ratio of 25%-31%, and the particle size of 1-0.088 mm has a ratio of 11%-15%; The fused magnesia grain size of 1 to 0.088 mm is 10%; the grain size of ≤ 0.088 mm is 10% to 20%; The graphite particle size is ≤100 mesh; The zirconium oxide particle size is 1-0.088 mm, and the ratio is 1%-2%, and the particle size is ≤0.088 mm, and the ratio is 2%.
[0007] Preferably, a. The raw materials for preparing magnesium calcium zircon sand are high-quality dolomite light-burned powder and desiliconized zirconium powder, wherein the CaO content of the dolomite light-burned powder is greater than or equal to 30%, the MgO content is greater than or equal to 60%, and the amount of desiliconized zirconium powder added is 1% to 5%, wherein ZrO2 ≥ 90%; b. Prepare the ingredients according to the requirements in step a, press the balls in a ball press and then calcine them in a vertical kiln at a temperature above 1800°C using heavy oil.
[0008] Preferably, the mass fraction of each component in the magnesium-calcium-zirconium sand is MgO ≥ 55%, CaO ≥ 28%, ZrO2 ≥ 1%, and the bulk density is ≥ 3.22 g·cm-3.
[0009] Preferably, the composition of the fused magnesia includes MgO ≥ 97.3%, CaO ≤ 0.9%, Fe2O3 ≤ 0.7%, Al2O3 ≤ 0.4%, SiO2 ≤ 0.6%, and a bulk density ≥ 3.45 g·cm-3.
[0010] Preferably, the zirconium oxide powder comprises ZrO2≥94%, SiO2≤0.2%, Fe2O3≤0.1%, Al2O3≤0.1%, and bulk density≥3.5g·cm-3.
[0011] Preferably, the silicon carbide powder comprises SiC ≥ 99%, the sum of Fe2O3, Al2O3 and CaO is not more than 0.8%, and free carbon is not more than 0.1%.
[0012] Preferably, the nano-yttrium oxide highly dispersed particles include Y2O3≥99%, volume density≥4.9g·cm-3, and particle size range of 30nm-40nm.
[0013] Preferably, the C9 petroleum resin powder is required to have a softening point of ≥140°C, a particle size range of 150 mesh to 200 mesh, an acid value of ≤0.8 mgKOH / g, and an ash content of ≤0.08%.
[0014] Preferably, the graphite is flake graphite with a particle size range of 80 mesh to 100 mesh, fixed carbon ≥ 95%, and moisture ≤ 0.05%.
[0015] Preferably, the production method of magnesium calcium zirconium carbon bricks comprises the following steps: Step ① raw material crushing: the sintered magnesium calcium zircon sand and the fused magnesia sand are respectively crushed, screened and ground by a jaw crusher, an impact crusher, a roll crusher and a Raymond mill, the sintered magnesium calcium zircon sand is screened according to a particle size of 5-3 mm, 3-1 mm and 1-0.088 mm, and the fused magnesia sand is screened according to a particle size of 1-0.088 mm and ≤0.088 mm; Step 2. mixing: all raw materials are added into a high-speed sand mixer according to the weight percentage required for mixing, and the order of adding materials is as follows: first, sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 3-1mm, and 1-0.088mm, fused magnesia with a particle size of 1-0.088mm, zirconium oxide with a particle size of 1-0.088mm, and C9 petroleum resin powder are mixed for 3-5 minutes, urotropine is added and mixed for 1-2 minutes, anhydrous resin is added and mixed for 3-5 minutes, graphite is added and mixed for 3-5 minutes, and finally fused magnesia with a particle size of ≤0.088mm, zirconium oxide powder with a particle size of ≤0.088mm, silicon carbide powder, and nano yttrium oxide highly dispersed particles are added and mixed, and the material is discharged when the material temperature reaches 80°C; Step 3: Drying the material: The mixed clay material in step 2 is hoisted onto the drying platform for turning over and heat dissipation, and the molding is performed after the temperature drops to about 45°C; Step ④ Molding: Weigh the required weight of the material dried in step ③, put it into the mold of a brick press with a pressure of 1000 tons, and form it under high pressure after the material is evenly distributed. The pressurization system adopts the principle of light first and heavy later, and exhaust in the middle to prevent the occurrence of layer cracks and cracks; Step ⑤ Drying: Dry the bricks formed in step ④ and heat treat them in an electric drying kiln at 280°C for 12 hours; Step ⑥ sorting and packaging: After cooling the dried magnesium calcium zirconium carbon bricks in step ⑤, sort them to remove unqualified bricks, and vacuum pack the qualified bricks and put them into the finished product warehouse.
[0016] The present invention discloses a magnesium calcium zirconium carbon brick and a production method thereof, which have the following beneficial effects: The present invention uses sintered magnesium calcium zircon sand as the main raw material, which has better thermal shock stability than fused magnesium calcium zircon sand. Tiny pores can be seen in microstructure observation. It is sintered in a high-temperature vertical kiln above 1800°C using heavy oil as fuel. Lightly burned low-silicon high-calcium dolomite powder and desiliconized zirconium powder are mixed in proportion and then pressed into balls by a ball press at a pressure of 300MPa. The ball forming pressure must be greater than 300MPa, and the closed pores can be significantly reduced. The material is denser after sintering and has a higher volume density. Under high temperature conditions, magnesium oxide in the sintered magnesium calcium zircon sand can be dissolved into zirconium oxide crystals to form cubic stable zirconium oxide. The eutectic temperature of MgO-ZrO2 can reach 2070°C. There is no volume change after cooling, and the material can maintain a stable cubic structure without the generation of cracks. The nanometer yttrium oxide highly dispersed particles added in the present invention can reduce the phase transition temperature of martensite, make the zirconium oxide solid solution completely non-decomposed, and the melting point is as high as 2400°C, and has excellent properties such as good erosion resistance, high temperature resistance, and low thermal expansion. The added particle size is between 80-100nm, which can fill the pores, reduce the porosity of the surface and internal of the brick, enhance the anti-hydration performance of the brick, and can greatly increase the temperature range in which zirconium oxide is stable in the cubic crystal phase, and can significantly improve the thermal shock stability of the brick. The nanometer yttrium oxide highly dispersed particles react with O2 to form a protective film with an anti-oxidation effect on the surface of the brick, protect the easily oxidized part of the brick, and improve the anti-oxidation performance. At high temperatures, the nanometer yttrium oxide highly dispersed particles can change the internal structure and phase composition of the brick, reduce the reaction tendency to molten steel, slag and other substances, reduce chemical reactions, and increase the service life of the furnace.
[0017] The zirconium oxide added in the present invention contains 30% m-ZrO2 and 70% c-ZrO2. Studies have shown that such a ratio has the best thermal shock stability. When zirconium oxide changes from high temperature to low temperature, the tetragonal phase is converted to the monoclinic phase, and the volume changes, resulting in microcracks in the brick, thereby improving the thermal shock stability. ZrO2 has poor wettability to slag, preventing low-melting materials from corroding the matrix. Under high temperature conditions, zirconium oxide powder reacts with free calcium oxide to generate calcium zirconate that wraps around calcium oxide, increasing the brick's resistance to hydration and spalling. Silicon carbide, as an antioxidant, has the characteristics of high temperature resistance and wear resistance. The 325-mesh fine powder can fill pores, reduce apparent porosity, increase volume density, and make the brick have excellent corrosion resistance and scouring resistance. The magnesium-calcium-zirconium-carbon brick of the present invention has a wide range of applications, and is particularly suitable for parts with high requirements for thermal shock stability. It is suitable for various types of off-furnace refining furnaces, such as AOD furnaces and GOR converters, and has great promotion value.
[0018] The C9 petroleum resin powder added in the present invention has a high softening point and good thermal stability. It has high bonding performance and can significantly improve the apparent porosity, volume density, room temperature compressive strength, room temperature flexural strength and other indicators of the brick. A continuous film layer is formed on the surface of the brick, which can block the effects of harmful gases such as oxygen under high temperature and other use environments, protect flake graphite, silicon carbide, etc., and reduce erosion and penetration inside the brick. The formed dense structure can prevent the hydration of CaO at room temperature and provide certain protection for the brick. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0021] The embodiment of the present invention discloses a magnesium calcium zirconium carbon brick and a production method thereof. The present invention is described in detail below in conjunction with specific embodiments.
[0022] A magnesium calcium zirconium carbon brick is prepared by the following raw materials in weight ratio: 19% of sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 30% of sintered magnesium calcium zirconium sand with a particle size of 3-1mm, 11% of sintered magnesium calcium zirconium sand with a particle size of 1-0.088mm, 10% of fused magnesia sand with a particle size of 1-0.088mm, 15.8% of fused magnesia sand with a particle size of ≤0.088mm, 1% of zirconium oxide with a particle size of 1-0.088mm, 2% of zirconium oxide with a particle size of ≤0.088mm, 2% of -195 graphite, 1% of C9 petroleum resin powder, 4.6% of anhydrous resin, 0.4% of urotropine, 1% of silicon carbide powder, and 5% of nano yttrium oxide highly dispersed particles.
[0023] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks includes the following steps.
[0024] The mass fractions of the components in the magnesium-calcium-zirconium sand of the present invention are: MgO≥55%, CaO≥28%, ZrO2≥1%, and the bulk density is ≥3.22 g·cm-3.
[0025] The fused magnesia of the present invention comprises the following components: MgO≥97.3%, CaO≤0.9%, Fe2O3≤0.7%, Al2O3≤0.4%, SiO2≤0.6%, and a bulk density≥3.45g·cm-3.
[0026] The zirconium oxide powder of the present invention comprises the following components: ZrO2≥94%, SiO2≤0.2%, Fe2O3≤0.1%, Al2O3≤0.1%, and a bulk density≥3.5g·cm-3; The silicon carbide powder of the present invention comprises the following components: SiC≥99%, the sum of Fe2O3, Al2O3 and CaO not more than 0.8%, and free carbon not more than 0.1%.
[0027] The nanometer yttrium oxide highly dispersed particles of the present invention include Y2O3≥99%, volume density≥4.9g·cm-3, and particle size range of 80nm-100nm.
[0028] The C9 petroleum resin powder of the present invention is required to have a softening point of ≥140°C, a particle size range of 150 mesh to 200 mesh, an acid value of ≤0.8 mgKOH / g, and an ash content of ≤0.08%.
[0029] The graphite described in the present invention is flake graphite with a particle size range of 80-100 meshes, fixed carbon ≥ 95%, and moisture ≤ 0.05%.
[0030] The binder described in the present invention is an anhydrous resin, and the water content is required to be ≤0.3%.
[0031] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks comprises the following steps: Step ① raw material crushing: The sintered magnesium calcium zircon sand and the fused magnesia sand are respectively crushed, screened and ground by a jaw crusher, an impact crusher, a roll crusher and a Raymond mill, and the sintered magnesium calcium zircon sand is screened according to a particle size of 5-3 mm, 3-1 mm and 1-0.088 mm, and the fused magnesia sand is screened according to a particle size of 1-0.088 mm and ≤0.088 mm.
[0032] Step 2. mixing: all raw materials are added into a high-speed sand mixer according to the weight percentage required for mixing, and the order of adding materials is as follows: first, sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 3-1mm, and 1-0.088mm, fused magnesia with a particle size of 1-0.088mm, zirconium oxide with a particle size of 1-0.088mm, and C9 petroleum resin powder are mixed for 3-5 minutes, urotropine is added and mixed for 1-2 minutes, anhydrous resin is added and mixed for 3-5 minutes, graphite is added and mixed for 3-5 minutes, and finally, fused magnesia with a particle size of ≤0.088mm, zirconium oxide powder with a particle size of ≤0.088mm, silicon carbide powder and nano yttrium oxide high-dispersion particles are added to mix, and the material is discharged when the material temperature reaches 80°C.
[0033] Step ③ Drying: Hang the clay mixed in step ② onto the drying platform for turning over and heat dissipation, and shape it after the temperature drops to about 45°C.
[0034] Step ④ molding: weigh the required weight of the material dried in step ③, put it into the mold of a brick press with a pressure of 1000 tons, and shape it under high pressure after the material is evenly distributed. The pressurization system adopts the principle of light first and heavy later, and exhausting in the middle to prevent delamination and cracks.
[0035] Step ⑤ Drying: Dry the bricks formed in step ④ and place them in an electric drying kiln for heat treatment at 280°C for 12 hours.
[0036] Step ⑥ sorting and packaging: After cooling the dried magnesium calcium zirconium carbon bricks in step ⑤, sort them to remove unqualified bricks, and vacuum pack the qualified bricks and put them into the finished product warehouse.
[0037] A magnesium calcium zirconium carbon brick is prepared by the following raw materials in weight ratio: 35% of sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 24% of sintered magnesium calcium zirconium sand with a particle size of 3-1mm, 15% of sintered magnesium calcium zirconium sand with a particle size of 1-0.088mm, 7.8% of fused magnesium sand with a particle size of ≤0.088mm, 2% of zirconium oxide with a particle size of 1-0.088mm, 2% of zirconium oxide with a particle size of ≤0.088mm, 5% of -195 graphite, 1.5% of C9 petroleum resin powder, 4.6% of anhydrous resin, 0.2% of urotropine, 0.5% of silicon carbide powder, and 3% of nano yttrium oxide highly dispersed particles.
[0038] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks includes the following steps.
[0039] The mass fractions of the components in the magnesium-calcium-zirconium sand of the present invention are: MgO≥55%, CaO≥28%, ZrO2≥1%, and the bulk density is ≥3.22 g·cm-3.
[0040] The fused magnesia of the present invention comprises the following components: MgO≥97.3%, CaO≤0.9%, Fe2O3≤0.7%, Al2O3≤0.4%, SiO2≤0.6%, and a bulk density≥3.45g·cm-3.
[0041] The zirconium oxide powder of the present invention comprises the following components: ZrO2≥94%, SiO2≤0.2%, Fe2O3≤0.1%, Al2O3≤0.1%, and a bulk density≥3.5g·cm-3; The silicon carbide powder of the present invention comprises the following components: SiC≥99%, the sum of Fe2O3, Al2O3 and CaO not more than 0.8%, and free carbon not more than 0.1%.
[0042] The nanometer yttrium oxide highly dispersed particles of the present invention include Y2O3≥99%, volume density≥4.9g·cm-3, and particle size range of 80nm-100nm.
[0043] The C9 petroleum resin powder of the present invention is required to have a softening point of ≥140°C, a particle size range of 150 mesh to 200 mesh, an acid value of ≤0.8 mgKOH / g, and an ash content of ≤0.08%.
[0044] The graphite described in the present invention is flake graphite with a particle size range of 80-100 meshes, fixed carbon ≥ 95%, and moisture ≤ 0.05%.
[0045] The binder described in the present invention is an anhydrous resin, and the water content is required to be ≤0.3%.
[0046] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks comprises the following steps: Step ① raw material crushing: The sintered magnesium calcium zircon sand and the fused magnesia sand are respectively crushed, screened and ground by a jaw crusher, an impact crusher, a roll crusher and a Raymond mill, and the sintered magnesium calcium zircon sand is screened according to a particle size of 5-3 mm, 3-1 mm and 1-0.088 mm, and the fused magnesia sand is screened according to a particle size of 1-0.088 mm and ≤0.088 mm.
[0047] Step 2. mixing: all raw materials are added into a high-speed sand mixer according to the weight percentage required for mixing, and the order of adding materials is as follows: first, sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 3-1mm, and 1-0.088mm, fused magnesia with a particle size of 1-0.088mm, zirconium oxide with a particle size of 1-0.088mm, and C9 petroleum resin powder are mixed for 3-5 minutes, urotropine is added and mixed for 1-2 minutes, anhydrous resin is added and mixed for 3-5 minutes, graphite is added and mixed for 3-5 minutes, and finally, fused magnesia with a particle size of ≤0.088mm, zirconium oxide powder with a particle size of ≤0.088mm, silicon carbide powder and nano yttrium oxide high-dispersion particles are added to mix, and the material is discharged when the material temperature reaches 80°C.
[0048] Step ③ Drying: Hang the clay mixed in step ② onto the drying platform for turning over and heat dissipation, and shape it after the temperature drops to about 45°C.
[0049] Step ④ molding: weigh the required weight of the material dried in step ③, put it into the mold of a brick press with a pressure of 1000 tons, and shape it under high pressure after the material is evenly distributed. The pressurization system adopts the principle of light first and heavy later, and exhausting in the middle to prevent delamination and cracks.
[0050] Step ⑤ Drying: Dry the bricks formed in step ④ and place them in an electric drying kiln for heat treatment at 280°C for 12 hours.
[0051] Step ⑥ sorting and packaging: After cooling the dried magnesium calcium zirconium carbon bricks in step ⑤, sort them to remove unqualified bricks, and vacuum pack the qualified bricks and put them into the finished product warehouse.
[0052] A magnesium calcium zirconium carbon brick is prepared by the following raw materials in weight ratio: 36% of sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 25% of sintered magnesium calcium zirconium sand with a particle size of 3-1mm, 11% of sintered magnesium calcium zirconium sand with a particle size of 1-0.088mm, 7.8% of fused magnesium sand with a particle size of ≤0.088mm, 2% of zirconium oxide with a particle size of 1-0.088mm, 2% of zirconium oxide with a particle size of ≤0.088mm, 7% of -195 graphite, 1.5% of C9 petroleum resin powder, 4.6% of anhydrous resin, 0.2% of urotropine, 0.5% of silicon carbide powder, and 6% of nano yttrium oxide highly dispersed particles.
[0053] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks includes the following steps.
[0054] The mass fractions of the components in the magnesium-calcium-zirconium sand of the present invention are: MgO≥55%, CaO≥28%, ZrO2≥1%, and the bulk density is ≥3.22 g·cm-3.
[0055] The fused magnesia of the present invention comprises the following components: MgO≥97.3%, CaO≤0.9%, Fe2O3≤0.7%, Al2O3≤0.4%, SiO2≤0.6%, and a bulk density≥3.45g·cm-3.
[0056] The zirconium oxide powder of the present invention comprises the following components: ZrO2≥94%, SiO2≤0.2%, Fe2O3≤0.1%, Al2O3≤0.1%, and a bulk density≥3.5g·cm-3; The silicon carbide powder of the present invention comprises the following components: SiC≥99%, the sum of Fe2O3, Al2O3 and CaO not more than 0.8%, and free carbon not more than 0.1%.
[0057] The nanometer yttrium oxide highly dispersed particles of the present invention include Y2O3≥99%, volume density≥4.9g·cm-3, and particle size range of 80nm-100nm.
[0058] The C9 petroleum resin powder of the present invention is required to have a softening point of ≥140°C, a particle size range of 150 mesh to 200 mesh, an acid value of ≤0.8 mgKOH / g, and an ash content of ≤0.08%.
[0059] The graphite described in the present invention is flake graphite with a particle size range of 80-100 meshes, fixed carbon ≥ 95%, and moisture ≤ 0.05%.
[0060] The binder described in the present invention is an anhydrous resin, and the water content is required to be ≤0.3%.
[0061] The above-mentioned method for manufacturing magnesium calcium zirconium carbon bricks comprises the following steps: Step ① raw material crushing: The sintered magnesium calcium zircon sand and the fused magnesia sand are respectively crushed, screened and ground by a jaw crusher, an impact crusher, a roll crusher and a Raymond mill, and the sintered magnesium calcium zircon sand is screened according to a particle size of 5-3 mm, 3-1 mm and 1-0.088 mm, and the fused magnesia sand is screened according to a particle size of 1-0.088 mm and ≤0.088 mm.
[0062] Step 2. mixing: all raw materials are added into a high-speed sand mixer according to the weight percentage required for mixing, and the order of adding materials is as follows: first, sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 3-1mm, and 1-0.088mm, fused magnesia with a particle size of 1-0.088mm, zirconium oxide with a particle size of 1-0.088mm, and C9 petroleum resin powder are mixed for 3-5 minutes, urotropine is added and mixed for 1-2 minutes, anhydrous resin is added and mixed for 3-5 minutes, graphite is added and mixed for 3-5 minutes, and finally, fused magnesia with a particle size of ≤0.088mm, zirconium oxide powder with a particle size of ≤0.088mm, silicon carbide powder and nano yttrium oxide high-dispersion particles are added to mix, and the material is discharged when the material temperature reaches 80°C.
[0063] Step ③ Drying: Hang the clay mixed in step ② onto the drying platform for turning over and heat dissipation, and shape it after the temperature drops to about 45°C.
[0064] Step ④ molding: weigh the required weight of the material dried in step ③, put it into the mold of a brick press with a pressure of 1000 tons, and shape it under high pressure after the material is evenly distributed. The pressurization system adopts the principle of light first and heavy later, and exhausting in the middle to prevent delamination and cracks.
[0065] Step ⑤ Drying: Dry the bricks formed in step ④ and place them in an electric drying kiln for heat treatment at 280°C for 12 hours.
[0066] Step ⑥ sorting and packaging: After cooling the dried magnesium calcium zirconium carbon bricks in step ⑤, sort them to remove unqualified bricks, and vacuum pack the qualified bricks and put them into the finished product warehouse.
[0067] The physical and chemical indicators of the magnesium-calcium-titanium-carbon bricks described in the above embodiments are as follows:
[0068] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A magnesium calcium zirconium carbon brick, characterized in that: Made from the following raw materials and their weight ratios: Sintered magnesium calcium zirconium sand 60% ~ 80%; Fused magnesia 10% to 30%; Zirconia 2% to 4%; Silicon carbide powder 0.5%~3%; Nano yttrium oxide highly dispersed particles 2% to 6%; C9 petroleum resin powder 1%~2%; Graphite 2% to 7%; Binder 4% to 6%; Hexamethylenetetramine 0.3% to 0.5%; Wherein: the sintered magnesium calcium zirconium sand with a particle size of 5-3 mm has a ratio of 19%-36%, the particle size of 3-1 mm has a ratio of 25%-31%, and the particle size of 1-0.088 mm has a ratio of 11%-15%; The fused magnesia grain size of 1 to 0.088 mm is 10%; the grain size of ≤ 0.088 mm is 10% to 20%; The graphite particle size is ≤100 mesh; The zirconium oxide particle size is 1-0.088 mm, and the ratio is 1%-2%, and the particle size is ≤0.088 mm, and the ratio is 2%.
2. A magnesium calcium zirconium carbon brick according to claim 1, characterized in that: a. The raw materials for preparing magnesium calcium zircon sand are high-quality dolomite light-burned powder and desiliconized zirconium powder. The CaO content of the dolomite light-burned powder is greater than or equal to 30%, the MgO content is greater than or equal to 60%, and the amount of desiliconized zirconium powder added is 1% to 5%, of which ZrO2 is ≥90%; b. Prepare the ingredients according to the requirements in step a, press the balls in a ball press and then calcine them in a vertical kiln at a temperature above 1800°C using heavy oil.
3. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The mass fractions of the components in the magnesium-calcium-zirconium sand are MgO≥55%, CaO≥28%, ZrO2≥1%, and the bulk density is ≥3.22 g·cm-3.
4. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The fused magnesia comprises the following components: MgO≥97.3%, CaO≤0.9%, Fe2O3≤0.7%, Al2O3≤0.4%, SiO2≤0.6%, and a bulk density≥3.45g·cm-3.
5. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The zirconium oxide powder comprises the following components: ZrO2≥94%, SiO2≤0.2%, Fe2O3≤0.1%, Al2O3≤0.1%, and bulk density≥3.5g·cm-3.
6. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The silicon carbide powder comprises: SiC ≥ 99%, the sum of Fe2O3, Al2O3 and CaO is not more than 0.8%, and free carbon is not more than 0.1%.
7. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The nanometer yttrium oxide highly dispersed particles include: Y2O3≥99%, volume density≥4.9g·cm-3, and particle size range of 30nm-40nm.
8. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The C9 petroleum resin powder is required to have a softening point of ≥140°C, a particle size range of 150 mesh to 200 mesh, an acid value of ≤0.8 mgKOH / g, and an ash content of ≤0.08%.
9. The magnesium calcium zirconium carbon brick according to claim 1, characterized in that: The graphite is flake graphite with a particle size ranging from 80 meshes to 100 meshes, fixed carbon ≥ 95%, and moisture ≤ 0.05%.
10. The method for producing magnesium calcium zirconium carbon bricks according to any one of claims 1 to 9, characterized in that: The steps include: Step ① raw material crushing: the sintered magnesium calcium zircon sand and the fused magnesia sand are respectively crushed, screened and ground by a jaw crusher, an impact crusher, a roll crusher and a Raymond mill, the sintered magnesium calcium zircon sand is screened according to a particle size of 5-3 mm, 3-1 mm and 1-0.088 mm, and the fused magnesia sand is screened according to a particle size of 1-0.088 mm and ≤0.088 mm; Step 2. mixing: all raw materials are added into a high-speed sand mixer according to the weight percentage required for mixing, and the order of adding materials is as follows: first, sintered magnesium calcium zirconium sand with a particle size of 5-3mm, 3-1mm, and 1-0.088mm, fused magnesia with a particle size of 1-0.088mm, zirconium oxide with a particle size of 1-0.088mm, and C9 petroleum resin powder are mixed for 3-5 minutes, urotropine is added and mixed for 1-2 minutes, anhydrous resin is added and mixed for 3-5 minutes, graphite is added and mixed for 3-5 minutes, and finally fused magnesia with a particle size of ≤0.088mm, zirconium oxide powder with a particle size of ≤0.088mm, silicon carbide powder, and nano yttrium oxide highly dispersed particles are added and mixed, and the material is discharged when the material temperature reaches 80°C; Step 3: Drying the material: The mixed clay material in step 2 is hoisted onto the drying platform for turning over and heat dissipation, and the molding is performed after the temperature drops to about 45°C; Step ④ Molding: Weigh the required weight of the material dried in step ③, put it into the mold of a brick press with a pressure of 1000 tons, and form it under high pressure after the material is evenly distributed. The pressurization system adopts the principle of light first and heavy later, and exhaust in the middle to prevent the occurrence of layer cracks and cracks; Step ⑤ Drying: Dry the bricks formed in step ④ and heat treat them in an electric drying kiln at 280°C for 12 hours; Step ⑥ sorting and packaging: After cooling the dried magnesium calcium zirconium carbon bricks in step ⑤, sort them to remove unqualified bricks, and vacuum pack the qualified bricks and put them into the finished product warehouse.
Citation Information
Patent Citations
Calcium oxide carbon brick and preparation method thereof
CN104829252A
Zirconium composite high-performance electrofused magnesium-calcium zirconium brick and manufacturing method thereof
CN107434404A
Anti-stripping unfired magnesia-calcium-carbon brick and preparation method thereof
CN112341161A
Production method of anti-stripping unfired magnesia-calcium-carbon brick
CN116354702A
Hydration-resistant and erosion-resistant low-carbon unfired magnesia-calcium-carbon brick and manufacturing method thereof
CN118851729A
Cited By
Anti-hydration magnesite brick and preparation method thereof
CN120518384A
A hydration-resistant magnesium brick and its preparation method
CN120518384B